Benzonorcorrole NiII Complexes: Enhancement of Paratropic Ring Current and Singlet Diradical Character by Benzo‐Fusion. (24th January 2018) - Yoshida, Takuya; Takahashi, Kohtaro; Ide, Yuki; Kishi, Ryohei; Fujiyoshi, Jun‐ya; Lee, Sangsu; Hiraoka, Yuya; Kim, Dongho; Nakano, Masayoshi; Ikeue, Takahisa; Yamada, Hiroko; Shinokubo, Hiroshi
Abstract: Fused benzene rings to antiaromatic compounds generally improve their stability but attenuate their antiaromaticity. The opposite case is now reported. Ni II benzonorcorroles were synthesized and the effect of benzo‐fusion on the antiaromaticity was elucidated. The benzo‐fusion resulted in significant decrease of the HOMO–LUMO gaps and enhancement of the paratropic ring current effect. Furthermore, the introduction of the benzo groups induced singlet diradical character in the antiaromatic porphyrinoid.